Polygenic Risk Score Prediction for Endometriosis - Kloeve-Mogensen, Kirstine; Rohde, Palle Duun; Twisttmann, Simone; Nygaard, Marianne; Koldby, Kristina Magaard; Steffensen, Rudi; Dahl, Christian Møller; Rytter, Dorte; Overgaard, Michael Toft; Forman, Axel; Christiansen, Lene; Nyegaard, Mette (Frontiers in Reproductive Health, 2021)
Endometriosis is a major health care challenge because many young women with endometriosis go undetected for an extended period, which may lead to pain sensitization. Clinical tools to better identify candidates for laparoscopy-guided diagnosis are urgently needed. Since endometriosis has a strong genetic component, there is a growing interest in using genetics as part of the clinical risk assessment. The aim of this work was to investigate the discriminative ability of a polygenic risk score (PRS) for endometriosis using three different cohorts: surgically confirmed cases from the Western Danish endometriosis referral Center (249 cases, 348 controls), cases identified from the Danish Twin Registry (DTR) based on ICD-10 codes from the National Patient Registry (140 cases, 316 controls), and replication analysis in the UK Biobank (2,967 cases, 256,222 controls). Patients with adenomyosis from the DTR (25 cases) and from the UK Biobank (1,883 cases) were included for comparison. The PRS was derived from 14 genetic variants identified in a published genome-wide association study with more than 17,000 cases. The PRS was associated with endometriosis in surgically confirmed cases [odds ratio (OR) = 1.59, p = 2.57× 10−7] and in cases from the DTR biobank (OR = 1.50, p = 0.0001). Combining the two Danish cohorts, each standard deviation increase in PRS was associated with endometriosis (OR = 1.57, p = 2.5× 10−11), as well as the major subtypes of endometriosis; ovarian (OR = 1.72, p = 6.7× 10−5), infiltrating (OR = 1.66, p = 2.7× 10−9), and peritoneal (OR = 1.51, p = 2.6 × 10−3). These findings were replicated in the UK Biobank with a much larger sample size (OR = 1.28, p < 2.2× 10−16). The PRS was not associated with adenomyosis, suggesting that adenomyosis is not driven by the same genetic risk variants as endometriosis. Our results suggest that a PRS captures an increased risk of all types of endometriosis rather than an increased risk for endometriosis in specific locations. Although the discriminative accuracy is not yet sufficient as a stand-alone clinical utility, our data demonstrate that genetics risk variants in form of a simple PRS may add significant new discriminatory value. We suggest that an endometriosis PRS in combination with classical clinical risk factors and symptoms could be an important step in developing an urgently needed endometriosis risk stratification tool.